Never again, no more. 2 : getting back to me - Untamed, 1979- (Urban renaissance., 2021)
"As Lucinda, LaMeka, Charice, and Trinity struggle to turn their lives around, they each hit a crossroads. Despite their surmounting troubles, they still hope for a better life. But what will they sacrifice for a chance at a life they've always dreamed of? And at what costs? Will they decide to succumb to their situations, or will they learn how to truly say Never Again, No More?"